Determinant of Waqif Decisions in Cash Waqf Donating Through Dompet Dhuafa South Sulawesi in Makassar City - Rahim, Adhira Imawardhani; Awaluddin, Murtiadi; Ambo Masse, Rahman (Management of Zakat and Waqf Journal (MAZAWA), 2024)
waqf is one of the philanthropic instruments in Islam that allows Muslims to donate their assets for public benefit in a sustainably. However, public participation in this practice is relatively limited. The fundamental objective of this study is to identify and analyse the determinants of Dompet Dhuafa South Sulawesi cash waqf in Makassar City. This study incorporates the Theory of Planned Behaviour, coupled with external variables, such as trust and waqf literacy. Questionnaires distributed to 80 respondents were used to collect data. Data analysis used various statistical tests, namely, partial, simultaneous and determinant tests. The results show that attitudes and subjective norms have no effect on waqf decisions. However, perceived behavioural control, trust, and waqf literacy influence this decision. In addition, this study concludes that trust in waqf institutions is the strongest predictor of waqf decisions. The research findings that attitude, subjective norms, perceived behavioural control, trust, and waqf literacy each contribute 43.35%. These findings provide strategic insights for Dompet Dhuafa South Sulawesi in designing more effective programmes and campaigns. The emphasis on trust and waqf literacy suggests that the organisation needs to develop communication and education strategies to increase people's trust and knowledge about waqf.